The Influence of Leadership Style, Motivation, and Work Environment on Teacher Performance - Yulia Nurmalasari; Hendarman Hendarman; Farida Wulandari (Journal of General Education and Humanities, 2026)
Background and Objective: This study addresses critical learning losses in Indonesian early childhood education (PAUD) following the COVID-19 pandemic, exacerbated by a 25% teacher turnover rate in private institutions. The research examines the direct and indirect effects of school principals' transformational leadership style, teacher work motivation, and work environment on overall teacher performance in private kindergartens, with motivation hypothesised as a mediating mechanism. Method: A quantitative correlational survey design was employed across 26 private kindergartens in Cibinong, Bogor Regency, Indonesia. The study population comprised 169 permanent foundation teachers, and the final sample of 119 respondents was determined using Slovin's formula (e = 0.05) and proportional random sampling. Data were collected using validated 5-point Likert-scale questionnaires measuring four constructs: teacher performance (36 items), leadership style (36 items), work motivation based on Maslow's hierarchy (36 items), and work environment—both physical and non-physical aspects (36 items). All instruments demonstrated high reliability (Cronbach's Alpha >0.97). Data analysis employed descriptive statistics, classical assumption testing, multiple regression analysis, path analysis with Sobel testing for indirect effects, and SITOREM (Scientific Iterative Tabulation-Oriented Educational Recommendation Method) for prioritised intervention recommendations. SPSS version 26 was used for all statistical analyses. Results: The path analysis model explained 79.6% of the variance in teacher performance (R²=0.796). Work motivation exhibited the strongest direct effect (βy2=0.392, p<0.001), followed by principal leadership style (βy1=0.284, p<0.001) and work environment (βy3=0.215, p=0.002). Work motivation significantly mediated both the leadership effect (indirect path βy12=0.142, p<0.001) and environmental effect (indirect path βy32=0.117, p<0.001), confirming its central role in performance outcomes. SITOREM analysis identified three priority interventions: a 50% increase in teacher honoraria to address physiological and self-actualisation gaps; transformational leadership training to strengthen team development and communication; and non-physical environmental improvements, including career counselling and organisational culture development, to reduce turnover